(untitled) (Comparatismi, 2022)
Aldous Huxley gained fame as the most cultivated and complex writer of his time. After the publication of Brave New World in 1932 his work became increasingly difficult to categorize as it began to cross the boundaries that separate art from science, religion and mysticism. Throughout his literary life he asked us to shift «our collective attention from the merely political to the basic biological aspects of the human situation». He urges us to shift from a nationalistic, warmongering way of thinking to an ecological approach: «Do we propose to live in this planet in symbiotic harmony with our environment? Or, preferring to be wantonly stupid, shall we choose to live like murderous and suicidal parasites that kill their host and so destroy themselves?» (The Politics of Ecology). He saw the ecological issues he dealt with as by-products of our world view, anticipating what environmentalists later defined as the ‘belief paradigm’ of our culture (Sawyer 2008). This paper studies the link Aldous Huxley draws between this ‘belief paradigm’ and language and how, through a brand-new theory of language, he identifies a pathway out of the ecological trauma that Man has caused. It focuses, in particular, on the four essays he devoted entirely to this theme: Words and Behavior, 1936; Words and Their Meaning, 1940, On Language, 1959, and The Politics of Ecology. The Question of Survival (1963). The last section of this paper analyses the novel Island (1962). It is in this ‘utopian’ novel, in fact, that he explores in greater depth the themes touched upon in his previous essay-writing. Here the author combines language theory, human narrative talent and ecological concern to build a unique picture which is, arguably, his most important legacy to future generations.